Vaccine-elicited receptor-binding site antibodies neutralize two New World hemorrhagic fever arenaviruses - Clark, Lars E (2018)
Fil: Clark, Lars E. Department of Microbiology and Immunobiology, Harvard Medical School, Boston; Estados Unidos.